Automatic translation of C/C++ parallel code into synchronous formalism using an SSA intermediate form - Besnard, Loïc; Gautier, Thierry; Moy, Matthieu; Talpin, Jean-Pierre; Johnson, Kenneth; Maraninchi, Florence (Electronic Communications of the EASST, 2009)
We present an approach for the translation of imperative code (like C, C++) into the synchronous formalism Signal, in order to use a model-checker to verify properties on the source code. The translation uses SSA as an intermediate formalism, and the GCC compiler as a front-end. The contributions of this paper with respect to previous work are a more efficient translation scheme, and the management of parallel code. It is applied successfully on simple SystemC examples.